ENHANCED LATE GAS GENERATION POTENTIAL OF PETROLEUM SOURCE ROCKS VIA RECOMBINATION REACTIONS: EVIDENCE FROM THE NORWEGIAN NORTH SEA - Erdmann M.; Horsfield B. (My University, 2006)
Gas generation in the deep reaches of sedimentary basins is usually considered to take place via the primary cracking of short alkyl groups from overmature kerogen or the secondary cracking of petroleum. Here, we show that recombination reactions ultimately play the dominant role in controlling the timing of late gas generation in source rocks which contain mixtures of terrigeneous and marine organic matter. These reactions, taking place at low levels of maturation, result in the formation of a thermally stable bitumen, which is the major source of methane at very high maturities. The inferences come from pyrolysis experiments performed on samples of the Draupne Formation (liptinitic Type II kerogen) and Heather Formation (mixed marine-terrigeneous Type III kerogen), both Upper Jurassic source rocks stemming from the Norwegian northern North Sea Viking Graben system. Non-isothermal closed system micro scale sealed vessel (MSSV) pyrolysis, non-isothermal open system pyrolysis and Rock Eval type pyrolysis were performed on the solvent extracted, concentrated kerogens of the two immature samples. The decrease of C6+ products in the closed system MSSV pyrolysis provided the basis for the calculation of secondary gas (C1-5) formation. Subtraction of the calculated secondary gas from the total observed gas yields a "remaining" gas. In the case of the Draupne Formation this is equivalent to primary gas cracked directly from the kerogen, as detected by a comparison with multistep open pyrolysis data. For the Heather Formation the calculated remaining gas formation profile is initially attributable to primary gas but there is a second major gas pulse at very high temperature (>550 °C at 5.0 K min-1) that is not primary. This has been explained by a recondensation process where first formed high molecular weight compounds in the closed system yield a macromolecular material that undergoes secondary cracking at elevated temperatures. The experiments provided the input for determination of kinetic parameters of the different gas generation types, which were used for extrapolations to a linear geological heating rate of 10-11 K min-1. Peak generation temperatures for the primary gas generation were found to be higher for Heather Formation (Tmax = 190 °C, equivalent to Ro appr. 1.7%) compared to Draupne Formation (Tmax = 175 °C, equivalent to appr. Ro 1.3%). Secondary gas peak generation temperatures were calculated to be 220 °C for the Heather Formation and 205 to 215 °C for the Draupne Formation, respectively, with equivalent vitrinite reflectance values (Ro) between 2.4% and 2.0%. The high temperature secondary gas formation from cracking of the recombination residue as detected for the Heather Formation is quantitatively important and is suggested to occur at very high temperatures (Tmax approx. 250 °C) for geological heating rates. The prediction of a significant charge of dry gas from the Heather Formation at very high maturity levels has important implications for petroleum exploration in the region, especially to the north of the Viking Graben where Upper Jurassic sediments are sufficiently deep buried to have experienced such a process. ? 2006 Elsevier Inc. All rights reserved.
Keywords: ENHANCED OIL RECOVERY; HYDROCARBON GENERATION; PYROLYSIS; CALLUNA; Мезозой::Юрская; Mesozoic::Jurassic